Descortinando o cenário cultural na Paraíba representação da informação no correio das artes do jornal A União - Flôr, Ana Cristina Coutinho (2024)
The magazine Correio das Artes constitutes a potential source of information regarding art and culture in the State of Paraíba. This research aimed to study issues related to the representation of the information contained on the covers of Correio das Artes, produced by the centennial Paraíba newspaper A União. The magazine is the oldest in Paraíba in the field of art and culture, with over seventy years of publishing highlights in literature, music, cinema, visual arts, and other cultural segments. Therefore, the general objective is to represent the information contained on the covers of Correio das Artes through indexing, so that the collection can be efficiently retrieved by users. The specific objectives include creating thematic categories based on the subjects covered on the covers; defining the created thematic categories; and developing an explanatory manual on the established categories. For this purpose, the theoretical foundation was based on the fields of Information Representation and Thematic Representation of Information. Methodologically, the research is characterized as bibliographic and documentary, with a qualitative approach and applied nature. As a data collection instrument, Bardin's (2011) Content Analysis was employed on 166 copies of Correio das Artes magazines between the years 2010 and 2023. In the analysis, six main thematic categories were identified as recurring topics in these magazines: visual arts, cinema, photography, literature, music, and theater. The subcategories include: visual arts (biography), cinema (biography), photography (biography), literature (biography) and literature (cordel), music (biography), and theater (biography). To aid understanding of each category's meaning, an explanatory glossary of each term was developed. The cultural value that Correio das Artes holds for society is well-known, as a specialized magazine in the literary field that has helped foster the art and culture of the state of Paraíba for over seven decades, it stands as one of the oldest in this segment in Brazil, becoming an information source that required a recovery process to meet user needs, contributing to the newspaper A Uniao archive can preserve this collection and help maintain a portion of Paraíba’s memory.